Ectopic Pregnancy in Cesarean Section Scar - Firoozeh Ahmadi (International Journal of Fertility and Sterility, 2010)
Pregnancy implantation within the scar of a previous cesarean delivery is one of the rarest locations for an ectopic pregnancy. Early diagnosis of this condition with the use of ultrasound imaging allows for preserving the uterus and subsequent fertility. However, a delay in either diagnosis or treatment can lead to uterine rupture, hysterectomy and significant maternal morbidity. With increasing incidence of cesarean sections (CS) worldwide and more liberal use of transvaginal sonography (TVS) in early pregnancy, more cases of cesarean scar pregnancy (CSP) are diagnosed. Thus every woman with a previous CS presenting to the early pregnancy unit should have a routine check for the cesarean scar appearance. We present the case of a 34 year-old multigravid woman who was found to have an ectopic pregnancy in a cesarean scar at six weeks gestation, with significantly elevated beta-human chorionic gonadotrophin (Beta-hCG) level.